The Effect of Type of Roof on Heat Tolerance Coefficient and Milk Production in Friesian Holstein Crossbred Cows - Sucik Maylinda; F Riskila (Jurnal Ilmu-Ilmu Peternakan, 2023)
The type of the roof is one of the factors affecting dairy production, especially in the tropics. Many physiological mechanisms are affected by air temperature and humidity which is affected by the type of roofs. The objectives of the research were to determine the effect of type of roofs that are asbestos-roofed and tile-roofed on Heat Tolerance Coefficient (HTC) and milk production in Holstein Friesian Crossbred (FHC) cows. The research was conducted in 18th August to 20th Septembre 2022 in the traditional farms in Pandesari village, Pujon District, Malang Regency. Material used was 25 FHC cows from 4 farmers that have tile-roofed stall and 22 cows from 4 farmers who had asbestos-roofed stall. Research method was a field study with purposive sampling. Data were analyzed using an unpaired t-test using Minitab software 17 version. Results showed that the type of roof had a significant effect (P<0.05) on body temperature and milk production of FHC cows, but had no significant effect (P>0.05) on respiratory rates and HTC of FHC cattle. The air temperature of the tile-roofed cage was 21.88 ± 3.18 oC with humidity of 84.94 ± 13.18%, while the air temperature of the asbestos-roofed cage was 22.21 ± 3.40 °C with humidity of 73.94 ± 9.46 %. The body temperature of the FHC cow in the asbestos-roofed cage was 38.62 ± 0.46 oC while in the tile-roofed cage it was 38.33 ± 0.30°C. The respiratory rates of cows in asbestos-roofed cages was 38.01 ± 5.23 times/minute while in tile-roofed cages it was 36.14 ± 6.00 times/minute. HTC of cows in the asbestos-roofed cage was 2.66 ± 0.24 while in the tile-roofed cage it was 2.57 ± 0.26. Daily milk production of FHC cows in asbestos-roofed pens was 9.06 ± 4.23 liters/day/head while in tile-roofed pens it was 12.47 ± 3.84 liters/day/head.